Risk factors for neonatal bronchopulmonary dysplasia in extremely preterm premature rupture of membranes: a retrospective study - Eishin Nakamura; Shigetaka Matsunaga; Yoshihisa Ono; Yasushi Takai; Hiroyuki Seki (BMC, 2020)
Abstract Background Determination of the optimal timing for termination of pregnancy in cases of preterm premature rupture of membranes (pPROM) during the extremely preterm period is still difficult. Bronchopulmonary dysplasia (BPD) is a major disease widely taken into account when determining the prognosis of respiratory disorders in a neonate. Many aspects of this disease remain unclear. With the aim of further improving the prognosis of neonates born to mothers with pPROM, this study examined cases who were diagnosed with pPROM before 28 weeks of gestation. The study analysed risk factors for neonatal BPD. Methods This study included 73 subjects with singleton pregnancy, diagnosed with pPROM during the gestational period from 22 weeks and 0 days to 27 weeks and 6 days. The following factors were retrospectively examined: the gestational week at which pPROM was diagnosed, the gestational week at which delivery occurred, the period for which the volume of amniotic fluid was maintained, and neonatal BPD as a complication. Receiver operating characteristic (ROC) curve analyses were conducted to analyse the relationship of the onset of BPD with the duration of oligohydramnios and the gestational weeks of delivery. Results The mean gestational week at which a diagnosis of amniorrhexis was made was 24.5 ± 1.9 weeks (mean ± SD), and that at which delivery occurred was 27.0 ± 3.0 weeks. Fifty-seven cases (78.1%) were diagnosed with oligohydramnios, the mean duration of which was 17.4 ± 20.5 days. The mean birth weight of neonates was 1000 ± 455 g, of which 49 (67.1%) were diagnosed with BPD following birth. No neonates died in this study. The ROC curve indicated that the cut-off values for the duration of oligohydramnios and gestational age at delivery were 4 days and 24.1 weeks, respectively. Multivariate analysis indicated that the duration of oligohydramnios for more than 4 days before delivery and preterm delivery at less than 24.1 weeks were risk factors for the onset of BPD. Conclusions Our findings suggest that duration of oligohydramnios for more than 4 days before delivery and preterm delivery less than 24.1 weeks are risk factors for BPD in cases who are diagnosed with pPROM before 28 weeks of gestation.